Born to be asocial: newly hatched tortoises avoid unfamiliar individuals. (April 2018) - Versace, Elisabetta; Damini, Silvia; Caffini, Matteo; Stancher, Gionata
Abstract : Recognition of familiar individuals is important for modulating social interactions, but it is not clear to what extent this capacity depends on experience gained through repeated interactions with different animals. In wild tortoises, evidence of social interactions is limited to behaviours performed years after hatching, in the context of mating. To investigate the capacity to recognize familiar individuals at the onset of life in tortoises, we used hatchlings of two species ( Testudo marginata, Testudo graeca ) reared with a single conspecific as their unique social experience. When in a novel environment with the familiar conspecific, tortoises reached the distance expected after running random trajectories. In contrast, tortoises tested with an unfamiliar conspecific first explored the other tested individual, then actively kept a distance from it significantly larger than expected by chance. These results show evidence of spontaneous recognition of familiar individuals in a nonsocial species at the onset of life, and active avoidance of unfamiliar conspecifics. We suggest that this predisposition might be adaptive for young tortoises' dispersal and that evolutionary pressures for social behaviour might be relevant for nonsocial species even at the onset of life. Highlights: Tortoises recognize familiar conspecifics at the onset of life. Tortoise hatchlings actively avoid unfamiliar conspecifics. Spontaneous avoidance of unfamiliar conspecifics might help dispersal. Even in the absence of parental care, early social responses are important.